Demographic and socio-economic factors affecting birth preparation and complication readiness (BPCR) practices in Nepal - Acharya, Sunil Kumar (Nepal Population Journal, 2018)
BPCR practices by women in Nepal are still low. Still a relatively high percentage of women do not make BPCR to its fullest extent. Researches in developing countries show that various demographic, social and economic factors influence the BPCR practices by pregnant women. This paper examines the likelihood of BPCR practices based on women’s demographic, social and economic status in Nepal. NDHS 2011 data set has been utilized by applying bivariate logistics regression analysis technique to examine the effects of these variables on BPCR practices in Nepal. The analysis result shows high variations and gaps in BPCR practice based on demographic, social and economic status of women. Against this finding the study recommends implementation of appropriate policy and program measures by the government and other agencies to address the existing variations and gaps in BPCR practices among subgroups of women in Nepal. Further research studies focusing on the existing barriers on BPCR practice need to be conducted in Nepal especially among the women who are disadvantaged and marginalized.